2009
DOI: 10.4103/0973-8258.49375
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and purification of caffeine fromCoffea arabicaL. andCamellia sinensisL.: A combination antibacterial study

Abstract: dione [ Figure 1], a white powdered, water soluble plant alkaloid, is found in many plant species such as coffee and green tea. Caffeine at submillimolar concentrations exerts a wide variety of physiological effects on different organisms [11] and has long been known to have numerous actions, [12] including inhibition of phosphodiesterases, thereby increasing intracellular cAMP, direct effects on intracellular calcium concentrations, indirect effects on intracellular calcium concentrations via membrane hyperpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
6
1
Order By: Relevance
“…Caffeine's effects on human health have been broadly studied (Cano-Marquina et al, 2013). Besides that, its antimicrobial properties have been examined against: human pathogens like Staphylococcus aureus, Klebsiella pneumonia, and Pseudomonas aeruginosa, constituents of natural human microflora such as Escherichia coli, Streptococcus oralis, and Propionibacterium acnes, but also Pseudomonas fluorescens and Bacillus subtilis that are present in terrestrial and aquatic habitats (Raj & Dhala, 1965;Ramanaviciene et al, 2003;Cogo et al, 2008, Mohammed & Al-Bayati, 2009. Researchers have also investigated the use of caffeine as a natural pesticide against insects, frogs, and slugs (Nathanson, 1984;Hollingsworth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine's effects on human health have been broadly studied (Cano-Marquina et al, 2013). Besides that, its antimicrobial properties have been examined against: human pathogens like Staphylococcus aureus, Klebsiella pneumonia, and Pseudomonas aeruginosa, constituents of natural human microflora such as Escherichia coli, Streptococcus oralis, and Propionibacterium acnes, but also Pseudomonas fluorescens and Bacillus subtilis that are present in terrestrial and aquatic habitats (Raj & Dhala, 1965;Ramanaviciene et al, 2003;Cogo et al, 2008, Mohammed & Al-Bayati, 2009. Researchers have also investigated the use of caffeine as a natural pesticide against insects, frogs, and slugs (Nathanson, 1984;Hollingsworth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with previous reports. Mohammed and Al-Bayati (2009) reported that MICs of caffeine coffee ranged between 62.5 and 250 µg/ml and green tea caffeine ranged from 62.5 to 500 µg/ml while Pruthviraj and coworkers (2011) reported MICs of caffeine isolated from tea between 65.5 and 250 µg/ml and green tea caffeine between 65.5 and 500 µg/ml. The activity of pure caffeine, used in this study, was further corroborated by Ramanaviciene and coworkers (2003b) who indicated that pure caffeine has a direct antibacterial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, caffeine inhibits muscle contraction (Youn et al, 1991), acts as the antagonist of the adenosine receptors to increase their plasmatic concentration (Conlay et al, 1997), potentiates the lethal effects of ionizing radiation which is important during the treatment of cancer (Sakurai et al, 1999), alters glucose metabolism (Greer et al, 2001), sensitizes calcium liberation channels and inhibits phosphodiesterase enzymes (Daly, 2007). Pure caffeine has antibacterial effect (Ramanaviciene et al, 2003a;Cogo et al, 2008;Mohammed & Al-Bayati, 2009), decreases the adherence of Streptococcus mutants to dental surface (Namboodiripad et al, 2007) and acts as the first dietary component able to protect one against Alzheimer's disease, Parkinson's disease and Huntington's disease (Ross et al, 2000;Lindsay et al, 2002;Ribeiro & Sebastiao, 2010). It increases the concentration of some immunocompetent cells and reinforces the activity of lysozyme to boost immunity against bacterial pathogens (Ramanaviciene et al, 2002;Ramanaviciene et al, 2003b;Vinod & Rangari, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed et al have performed liquid/liquid extraction of caffeine with dichloromethane, since it is the most widely used solvent for decaffeination. Their experience allowed recovering 98 to 99% of caffeine [54]. The efficiency of dichloromethane compared to ethyl acetate is supported by the experimental measurements of mole fraction solubility of caffeine in dichloromethane that is 10 times higher than the one in ethyl acetate [42].…”
Section: Influence Of Different Organic Solvents For Liquid/liquid Extraction Of Caffeinementioning
confidence: 99%